Desarrollo del Sistema de Información que soporta la Gestión de Procesos en la Dirección de Posgrado de la Universidad Técnica de Cotopaxi. Protocolo previo a la obtención de título en Magister en Sistema de Información. - Criollo Chanchicocha, Vilmer David (2020)
Technology has been advancing especially in the development of web applications, it is common to observe in institutions and companies applications that allow the automation of processes contributing to growth within a public and private entity. Through this project, a web application for process management was developed in the Postgraduate Directorate of the Technical University of Cotopaxi. This application was implemented with technologies such as Laravel, which is an open source framework, which allows the development of applications with PHP code in an elegant and simple way. The app makes it easy for students to make online registrations; In addition, it allows managing the selection and evaluation processes of the applicants, verifying the aptitude information for the master's degree; in turn, it also allows the student to enroll in a postgraduate program of the institution, and the management and control of grades and attendance; providing a better organization within the postgraduate department. MySql was used as the database manager, this tool allows hosting user data and defining custom functions through different languages such as PHP; for the development process, the agile SCRUM methodology was applied, which works with interactions to meet customer expectations. The methodology is flexible in the face of changes, allowing for easier construction of software with quality attributes.